(3TQM Gdabg GdcHQs - (3CMeO Hf eMeO, CHh GdefJgj, TgGH GdOjf GdeZfjSGhjs; (3GdfYeGf Hf KGHJ, GdJjej HGdhdGA, Gdchaj, CHh MfjaI,J (B150 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ CHhGdoefJgi Ef cJGH Gdabg GdCcHQ GdPj Ufag GdEeGe GdCYXe cJGH UMjM ebHhd s
(3BNQgG (B:s
(3Gddge jGgOj GdegJOjf EgOfG Edi UQGW eSJbje hUdi Gddg Ydi NjQ Ndbg eMeO hBdg CLeYjf JeJ s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B36 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B104s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfajs